2020
DOI: 10.3390/ijms21114136
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Alpha-Lipoic Acid on Salivary Dysfunction in a Mouse Model of Radioiodine Therapy-Induced Sialoadenitis

Abstract: Radioiodine (RI) therapy is known to cause salivary gland (SG) dysfunction. The effects of antioxidants on RI-induced SG damage have not been well described. This study was performed to investigate the radioprotective effects of alpha lipoic acid (ALA) administered prior to RI therapy in a mouse model of RI-induced sialadenitis. Four-week-old female C57BL/6 mice were divided into four groups (n = 10 per group): group I, normal control; group II, ALA alone (100 mg/kg); group III, RI alone (0.01 mCi/g body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In about 20-25% of thyroid cancer patients receiving therapeutic 131 I exposure, salivary gland damage of permanent nature is observed, leading to xerostomia and other dental problems affecting their quality of life 3,4 . It has been observed that other than the thyroid, the salivary glands are another major receiving port for concentrating 131 I, as it also shows the presence of sodium iodide symporter, which helps in transporting 131 I from blood to inside of thyrocytes 5 . This particularly is a cause of concern for 131 I treated patients as they have to bear the discomforts of the dry mouth for the rest of their life.…”
mentioning
confidence: 99%
“…In about 20-25% of thyroid cancer patients receiving therapeutic 131 I exposure, salivary gland damage of permanent nature is observed, leading to xerostomia and other dental problems affecting their quality of life 3,4 . It has been observed that other than the thyroid, the salivary glands are another major receiving port for concentrating 131 I, as it also shows the presence of sodium iodide symporter, which helps in transporting 131 I from blood to inside of thyrocytes 5 . This particularly is a cause of concern for 131 I treated patients as they have to bear the discomforts of the dry mouth for the rest of their life.…”
mentioning
confidence: 99%